A qualitative study on how to scaffold for collaborative learning in an innovative learning area, a student perspective - Trine Højberg Andersen; Guri Sivertsen Korpås (Uniped, 2022)
AbstractDiscussions and hands-on activities represent essential elements for student active learning, where students are engaged through group work and collaboration. This qualitative study gives insight into students’ experiences of activities designed for learning collaboratively and sheds light on how teachers can scaffold these activities. The constant comparative method has been applied to analyse focus-group interviews with students on a physics course for prospective engineering students. Different aspects that improve the collaboration in the learning process are found and discussed. Further, this research provides knowledge about how an innovative learning area designed for student active learning with technology such as an interactive screen can be used as part of the collaborative learning process, and how teachers can create an arena for cognitive apprenticeship in physics.